Phil Schiller admits that App Store algorithm needs improvement - Heisler, Yoni (Network World (Online), 2016)
[...]as the App Store exploded, coupled with Apple doling out billions upon billions of dollars to developers, Apple's online marketplace also became a place targeted by unscrupulous developers looking to make a quick buck via underhanded methods.